Poly(ethylene naphthalate) (PEN) / clay nanocomposites : preparation, structures and properties. - Chua, Yang Choo (2008)
This work is focused on the preparation of PEN/clay nanocomposites and the characterization of their structures and properties. The preparation of the nanocomposites by in-situ polymerization and melt intercalation was investigated, and the extent of clay dispersion at various length scales was examined by x-ray diffraction, polarizing optical microscopy and transmission electron microscopy. The dynamic mechanical properties and thermal stabilities of the nanocomposites were studied and correlated to their hierarchical structures. In addition to the direct stiffening effect of clay, it was found that the modified crystalline morphology, and the clay-induced orientation of the PEN lamellae/crystallites can also lead to additional reinforcement in the nanocomposites. Finally, the polymorphism behavior of the nanocomposites was investigated. The studies revealed that the temperature-dependent polymorphism behavior of the PEN/organoclay nanocomposites arises because the organoclays could simultaneously exert a hindered heterogeneous nucleating and plasticizing effect.